2011
DOI: 10.1037/a0022051
|View full text |Cite
|
Sign up to set email alerts
|

MRI correlates of cognitive impairment in childhood-onset multiple sclerosis.

Abstract: The robust association between cognitive function and reduced size of thalamus and global brain volume in pediatric-onset MS patients implicate neurodegenerative processes early in the disease course, and suggest that plasticity of an immature central nervous system is not sufficient to protect patients from the deleterious consequences of MS on cognitive neural networks. (PsycINFO Database Record (c) 2011 APA, all rights reserved).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
180
3
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(198 citation statements)
references
References 65 publications
11
180
3
1
Order By: Relevance
“…In one study, global brain volume loss in GM was correlated with lower estimated IQ and reduced information processing speed. 8 In another study, 16 more severe damage to GM, especially in the right precuneus and left middle temporal gyrus, was found in cognitively impaired as compared with cognitively preserved patients. In contrast with adult MS studies, using double inversion recovery sequences, the number and volume of cortical lesions (CL) did not differ between cognitively preserved (CL 12%) and impaired (CL 15%) pediatric patients.…”
Section: Mri Correlates Of Cognitive Impairmentmentioning
confidence: 92%
See 3 more Smart Citations
“…In one study, global brain volume loss in GM was correlated with lower estimated IQ and reduced information processing speed. 8 In another study, 16 more severe damage to GM, especially in the right precuneus and left middle temporal gyrus, was found in cognitively impaired as compared with cognitively preserved patients. In contrast with adult MS studies, using double inversion recovery sequences, the number and volume of cortical lesions (CL) did not differ between cognitively preserved (CL 12%) and impaired (CL 15%) pediatric patients.…”
Section: Mri Correlates Of Cognitive Impairmentmentioning
confidence: 92%
“…8 Using lesion probability mapping, Rocca et al 16 showed that cognitively impaired relative to cognitively preserved patients were more likely to harbor lesions in the right thalamus, middle and posterior corpus callosum, and bilateral parieto-occipital WM, implicating a posterior pattern of pathology that contributes to cognitive impairment in POMS.…”
Section: Mri Correlates Of Cognitive Impairmentmentioning
confidence: 99%
See 2 more Smart Citations
“…16 Time to further relapses is not established. EDSS, frequently used for secondary endpoints in adult studies, is typically low in children with MS, 8 18,19 Since accrual of physical disability is rarely observed in the pediatric age group, correlations between EDSS and MRI features may not be robust. Ongoing studies will clarify whether accrual of lesions in pediatric MS is an acceptable surrogate for clinical relapses in clinical trials.…”
Section: Resultsmentioning
confidence: 99%